Motivasi Intrinsik Dan Ekstrinsik Siswa Ekstrakurikuler Bolavoli Di SMP Negeri 9 Surabaya - Alva Rizki Ramadhandy; Made Pramono (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Motivation is an encouragement that a person has to do something that is intended or desired. The background of this study is that the researcher saw an increase in extracurricular bolavoli participants at SMP Negeri 9 Surabaya from 2022. Volleyball extracurricular activities are held 1x a week, students who take part in extracurricular activities always attend these exercises on Tuesdays without missing a single exercise not to attend, this proves that students have a strong interest and encouragement in participating in volleyball extracurricular activities at SMP Negeri 9 Surabaya. The purpose of this study was to determine the level of intrinsic and extrinsic motivation of extracurricular volleyball students at SMP Negeri 9 Surabaya. This study uses a quantitative descriptive type using a survey method, whose data is taken with a questionnaire. This study involved all students of SMP Negeri 9 Surabaya who participated in extracurricular volleyball activities totaling 30 students. This research was conducted on June 20, 2023 at SMP Negeri 9 Surabaya, using the total sampling technique. The results of this study in the intrinsic motivation factor show that volleyball extracurricular students at SMP Negeri 9 Surabaya are in the "Very Good" category by 57% (17 students) "Good" by 43% (13 students) "Less" 0% (0 students) "Very Less" 0% (0 students), while in extrinsic motivation in the "Very Good" category by 23.3% (7 students) "Good" by 60% (18 students) "Less" by 16.7% (5 students) "Very Less" by 0% (0 students). These results indicate that extracurricular volleyball students at SMP Negeri 9 Surabaya have a very important drive both from within and from outside. The results of the analysis show that intrinsic motivation is higher at 57% in the very good category while extrinsic motivation is 60% in the good category, this shows that intrinsic and extrinsic motivation are equally important to continue to encourage students to take part in extracurricular volleyball activities.